Staphylococcus aureus Causing Skin and Soft Tissue Infections in Companion Animals: Antimicrobial Resistance Profiles and Clonal Lineages - Costa, Sofia Santos (2022)
Staphylococcus aureus is a relevant agent of skin and soft tissue infections (SSTIs) in animals. Fifty-five S. aureus comprising all SSTI-related isolates in companion animals, collected between 1999 and 2018 (Lab 1) or 2017 and 2018 (Lab 2), were characterized regarding susceptibility to antibiotics and heavy metals and carriage of antimicrobial resistance determinants. Clonal lineages were established by PFGE, MLST and agr typing. Over half of the isolates (56.4%, 31/55) were methicillin-resistant S. aureus (MRSA), and 14.5% showed a multidrug resistance (MDR) phenotype. Resistance was most frequently observed for beta-lactams (81.8%, related to blaZ and/or mecA), fluoroquinolones (56.4%) and macrolides/lincosamides (14.5%, related to erm(A) or erm(C)). The distributions of heavy-metal MICs allowed the detection of non-wild-type populations associated with several resistance genes. The collection showed genetic diversity, with prevalence of clonal lineage ST22-agrI (45.5%, 25/55), comprising only MRSA isolates, and several less frequently detected clones, including ST5-agrII (14.6%, 8/55), ST398-agrI (9.1%, 5/55) and ST72-agrI (7.3%, 4/55). This work highlights the high frequency of SSTI-related MRSA strains that reflect the clonal lineages circulating both in companion animals and humans in Portugal, reinforcing the need for a One Health approach when studying staphylococci causing infections in companion animals.